Thrombin-Hirudin Complex Formation, Thrombin-Antithrombin III Complex Formation, and Thrombin Generation after Intrinsic Activation of Plasma - Gallistl, Siegfried; Muntean, Wolfgang (Thrombosis and Haemostasis, 1994)
To investigate the relative importance of direct inhibition of thrombin by complex formation and of inhibition of thrombin generation to the mechanisms by that unfractionated heparin (UH) and recombinant hirudin (rH) exert their anticoagulant effects, thrombin-antithrombin III complex (TAT) and thrombin-hirudin complex (THC) formation was compared with the generation of thrombin and prothrombin fragments 1 + 2 (F 1 + 2). Clotting was initiated by activation of citrated plasma in the absence or presence of UH or rH using partial thromboplastin, ellagic acid and calcium chloride. THC was determined by means of ELISA using specific antibodies to thrombin and rH.Activation of citrated plasma resulted in a sudden onset of thrombin generation after a lag phase of 2 min. Addition of 50 ng rH/ml plasma or 0.1 UH/ml plasma prolonged the clotting time to 3 min. While the peak of thrombin was only slightly decreased in hirudinized plasma, in heparinized plasma thrombin generation was significantly lower than in not anticoagulated plasma. This difference was more pronounced when the lag phase was prolonged to 5 min using 400 ng rH/ml plasma or 0.35 U UH/ml plasma. Using 1200 ng rH/ml or 0.65 U UH/ml to obtain a clotting time of 9 min only a small amount of thrombin could be detected in heparinized plasma, but hirudinized plasma still showed a high peak of thrombin. F 1 + 2 showed essentially the same pattern as thrombin. Prior to the onset of visible clot formation in all experiments using different concentrations of UH about the same values of TAT were observed. In contrast, when samples were anticoagulated with different amounts of rH, a dose dependent increase of THC was detected. When calculated from TAT and THC formation, much more thrombin was bound by rH than by AT III.Our experiments show that after intrinsic activation of plasma UH exerts its anticoagulant effect more by inhibiting thrombin generation, while rH suppresses thrombin generation to a much lesser extent but inhibits clotting more by direct inhibition of thrombin due to the formation of THC.